Tks5 Regulates Synaptic Podosome Formation and Stabilization of the Postsynaptic Machinery at the Neuromuscular Junction - Marcin Pęziński (MDPI AG, 2021)
Currently, the etiology of many neuromuscular disorders remains unknown. Many of them are characterized by aberrations in the maturation of the neuromuscular junction (NMJ) postsynaptic machinery. Unfortunately, the molecular factors involved in this process are still largely unknown, which poses a great challenge for identifying potential therapeutic targets. Here, we identified Tks5 as a novel interactor of αdystrobrevin-1, which is a crucial component of the NMJ postsynaptic machinery. Tks5 has been previously shown in cancer cells to be an important regulator of actin-rich structures known as invadosomes. However, a role of this scaffold protein at a synapse has never been studied. We show that Tks5 is crucial for remodeling of the NMJ postsynaptic machinery by regulating the organization of structures similar to the invadosomes, known as synaptic podosomes. Additionally, it is involved in the maintenance of the integrity of acetylcholine receptor (AChR) clusters and regulation of their turnover. Lastly, our data indicate that these Tks5 functions may be mediated by its involvement in recruitment of actin filaments to the postsynaptic machinery. Collectively, we show for the first time that the Tks5 protein is involved in regulation of the postsynaptic machinery.